2019
DOI: 10.22605/rrh5337
|View full text |Cite
|
Sign up to set email alerts
|

Powerless facing the wave of change: the lived experience of providing services in rural areas under the National Disability Insurance Scheme

Abstract: Introduction: Australia's National Disability Insurance Scheme (NDIS) is the catalyst for a significant shift in the delivery of disability services to people with a disability and their families, including those residing in rural and remote parts of Australia. Allied health services in rural areas of Australia are often limited, existing services are characterised as being of a generalist nature and demand for services often exceeds service capacity. This shift in the delivery of disability services with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…The diversity of responses of rural providers to the NDIS highlighted the diverse power relations at play. On the one hand, reflecting findings by Dintino et al (2019), participants described a sense of powerlessness to meet increased demand for boutique services or those requiring significant travel, time‐consuming preparation and non‐direct service activities. This suggests that broader health systems and geographical contexts influence rural providers' adaptability to change and possibly steer them toward a generalist care model to meet the needs of rural people with disability that are easily met but not those outside of these parameters, as seen in rural healthcare more generally (Mitchell et al 2018).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The diversity of responses of rural providers to the NDIS highlighted the diverse power relations at play. On the one hand, reflecting findings by Dintino et al (2019), participants described a sense of powerlessness to meet increased demand for boutique services or those requiring significant travel, time‐consuming preparation and non‐direct service activities. This suggests that broader health systems and geographical contexts influence rural providers' adaptability to change and possibly steer them toward a generalist care model to meet the needs of rural people with disability that are easily met but not those outside of these parameters, as seen in rural healthcare more generally (Mitchell et al 2018).…”
Section: Discussionmentioning
confidence: 64%
“…Of particular interest are the actions, resistance, changes and adaptations of rural providers to the NDIS implementation. A study by Dintino et al (2019) found rural health professionals employed by rural NDIS service providers felt powerless because they struggled to meet service demand in their community, and were limited in capacity to ensure individual people with disability received adequate service funding. Power (and powerlessness) is embedded in the other concepts and emerges through actions to change, resist and negotiate at each level.…”
Section: Framework Of Rural and Remote Healthmentioning
confidence: 99%
“…There were also reports of variation in service delivery and access within the region, with participants describing barriers to access for young people living in rural areas when compared to the urban centre. It could be that rural services have struggled to adapt to changes to service provision, following the introduction of the NDIS (Dintino, Wakely, Wolfgang, Wakely, & Little, 2019 ). Further research would be necessary to assess the effects of both the NDIS and regional variation in service delivery and access.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, allied health service providers delivering services under the NDIS have raised concerns about the potential for children to miss out on funding when their parents or carers had limited or no skills in understanding the system and advocating for their needs. 5 Geographic location was identified as a barrier to 'choice and control' of services for some individuals. 2,3 There is a shortage of disability services in rural and remote areas of Australia, and concerns have been raised about how these 'thin markets' will be able to cope with meeting the needs of people with a disability in their communities.…”
Section: Introductionmentioning
confidence: 99%